Investigation on the Hydrothermal Condition in Synthesis of Active Matrix from Metakaolin: Physicochemical Properties and Intrinsic Cracking Activities - Hudaya, Farhansyah Yusuf Putra; Anggaswara, Rezky Oktaviandy; Gunawan, Melia Laniwati; Kadja, Grandprix Thomryes Marth; Makertihartha, I. G. B. N. (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2024)
The current trends in research and development of FCC catalyst is focused on the formulation of active matrices that serve as pre-crackers, with the objective of reducing the diffusional resistance of the longer chain hydrocarbon molecule in the feed. In this study, an aluminosilicate active matrix was synthesised from metakaolin using hydrothermal method. The experimental variables that were varied were hydrothermal temperature, in the range of 80 to 110 °C, and hydrothermal time, in the range of 12 to 72 hours, to investigate the best conditions for synthesising the active matrix. Subsequently, the active matrix was subjected to a series of analyses, including X-ray fluorescence, X-ray diffraction, N2 physisorption, NH3-temperature programmed desorption, Fourier transform infrared spectroscopy, scanning electron microscopy and thermogravimetry, with the objective of determining its composition, crystal characteristics, surface characteristics, acidity, functional groups, material structure, and thermal characteristics. Additionally, the active matrix was tested for its intrinsic cracking activity using the micro activity test (MAT). The results indicate that the best temperature for hydrothermal synthesis of the active matrix is 80 °C. The active matrix synthesised with a heating time of 24 hours demonstrated the highest light cycle oil yield, reaching 38.9 wt%. Meanwhile, the active matrix synthesised at 48 hours exhibited the most favourable characteristics, with a specific surface area of 144.23 m2/g and a pore volume of 0.9933 cm3/g, as well as the highest cracking conversion of 70.0 wt%. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).